2015
DOI: 10.4236/jep.2015.68072
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Industrial Effluents and Their Effect on the Survival of Fish and Eutrophication of Lake Hawassa, Southern Ethiopia

Abstract: Growing trends in industrialization in Ethiopia have raised concerns about pollution of water bodies particularly of lakes. This study was therefore conducted to 1) characterize the chemical contents of major industrial effluents (namely textile ceramic and soft drink factories) that reached Lake Hawassa and 2) investigate the effects of the above mentioned factory effluents on survival of larvae fish and growth of algae. Effluent samples were collected from the outlet lagoons of each factory in December, 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The evidence is, the effects of textile factory effluents (5, 10 and 20% concentration levels) on the survival of tilapia fish fry killed high proportions of fish (65, 86.8 and 88.7%, respectively) compared to 16.1% mortality at 1% concentration level of the textile effluent. However, this is not quite different from that of the mortality rate in the control pond containing lake water of 9.4% (Berehanu et al, 2015). Besides, the consumption of the African big barb Labeobarbus intermedius whose catch is mainly from the rift valley lakes like Lake Hawassa and Lake Koka has declined.…”
Section: Effluent Discharges From the Textile Industriesmentioning
confidence: 77%
See 2 more Smart Citations
“…The evidence is, the effects of textile factory effluents (5, 10 and 20% concentration levels) on the survival of tilapia fish fry killed high proportions of fish (65, 86.8 and 88.7%, respectively) compared to 16.1% mortality at 1% concentration level of the textile effluent. However, this is not quite different from that of the mortality rate in the control pond containing lake water of 9.4% (Berehanu et al, 2015). Besides, the consumption of the African big barb Labeobarbus intermedius whose catch is mainly from the rift valley lakes like Lake Hawassa and Lake Koka has declined.…”
Section: Effluent Discharges From the Textile Industriesmentioning
confidence: 77%
“…The effluents from the textile factories contain high amount of organic and inorganic chemicals and are attributed to high Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Dissolved Solids (TDS), pH, Total Suspended Solids (TSS) values, and low dissolved oxygen (DO) values as well as the color change of the given water body as reported by Abrehet et al (2015). These make the textile industries one of the main sources of water pollution problems (Berehanu et al, 2015). For instance, a study made in Blue Nile River with respect to water quality parameters showed that the mean value of dissolved oxygen (DO) ranged from 3.7 mg/L at the site of waste water outlet of the Bahir Dar textile factory (Abrhet et al, 2015).…”
Section: Effluent Discharges From the Textile Industriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study the concentration of these metals exceeded WHO limit for drinking purpose. These might be due to the accumulation of these metals into the lake through effluent discharge from ceramic, textile and leather tanning industries located along the streams that fed into Tikurwuha River (Berehanu et al, 2015).…”
Section: Comparison Of Results With Previous Workmentioning
confidence: 99%
“…BOD) which can serve as "food" for microorganisms in the receiving body (Al-Mohammed et al, 2013;Ikhajiagbe et al, 2014;Rop et al, 2014). Microorganisms combine this matter with oxygen from the water to yield the energy they need to thrive and multiply; unfortunately, this oxygen is also needed by fish and other organisms in the river (Berehanu et al, 2015). Heavy organic pollution can lead to "dead zones" where no fish can be found; sudden releases of heavy organic loads that can cause sudden fishkills (Cuvin-Aralar et al, 2001;Stephanie et al, 2013).…”
Section: Wastewater Management Principlesmentioning
confidence: 99%